Spondylodiscitis Treated by Ozone Therapy (Ozone Therapy Global Journal, 2012)
The S pondylodiscitis is t he primary infection of the nucleus pu l posous in theintervertebral space, uncommon condition that can begin in the endplate cartilage andextend to the disk and adjacent vertebrae. It can occur after surgical procedures orspontaneously, the latter is the most common.Generally for the treatment of spondylodiscitis it has always been resorted to antibioticsalong with corsets or immobilization with orthopedic belts fortwo to three months, anda considerable percentage of 25 to 30% are invasive treatments, surgery is indicated,laminectomy or anterior retroperitoneal approach with instrumentation.I present the pioneering experience in the primary treatment of 13 cases of vertebralspondylodiscitis treated with the administration of oxygen-ozone mixture, from 2004to 2011. Thirteen cases of infection of the intervertebral space were observed; it wasdetermined that 9 cases were a spontaneous evolution and three post-surgical casesof herniat ed discs. The results after tr eat ment with ozon e discolysis paraverte bralpuncture followed by ozone have been very satisfactory.I t c an be concluded that primary treatment of o zone is showing excellent resultsobviating the use of corsets, especially antibiotics and surgery